Anterior attentional system efficacy in Parkinson’s disease: a cross-sectional study in Poland - Golińska-Drobienko, Paulina Beata; Sawicki, Artur; Bieleninik, Łucja; Schinwelski, Michał; Bidzan, Mariola (Frontiers in Human Neuroscience, 2025)
IntroductionCognitive impairment is a prevalent nonmotor symptom of Parkinson’s disease (PD), significantly affecting patients’ quality of life. Considering the gap in understanding the relationship between cognitive impairments in Parkinson’s disease and executive function, this study aimed to investigate the association between three cognitive statutes: normal cognition condition (PD-NCC), mild cognitive impairment (PD-MCI), and mild dementia (PDD), and the performance of the Anterior Attentional System in individuals with Parkinson’s disease.MethodsThis cross-sectional study included 96 participants with Parkinson’s disease (45 with PD-NCC, 39 with PD-MCI, and 12 with PDD) and 46 participants from control group, recruited between 2020 and 2023. MDS-UPDRS was used during the neurological examination. To assess cognitive status, we used: Mini-Mental State Examination, Californian Verbal Learning Test, Digit Span Test, Rey Complex Figure, and Trail Making Test (A and B form). The ROtman Baycrest Battery was employed to evaluate the Anterior Attentional System.ResultsParticipants with PDD exhibited significant impairments in the Anterior Attentional System. Energization impairment was observed in PD-MCI and PDD, though mildly. Monitoring and task-setting processes were notably impaired only in individuals with PDD, while these functions remained intact in those with PD-NCC and PD-MCI.ConclusionThe Anterior Attentional System is well-preserved in PD-NCC and PD-MCI however notably disturbed in PDD.